Assessment of the Impact of Dental Amalgam on Human Health: A Literature Review - Luchowska, Anna; Sroczyńska, Monika; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction: Dental amalgam is a dental material that has been used to fill carious cavities for more than 150 years. Amalgam fillings contain about 50% mercury and a mixture of other metals. The mercury it contains is controversial and debated by many researchers, as there is evidence of its negative effects on the human body. The constant release of mercury vapor from amalgam fillings is causing more and more countries to discontinue its use in treating patients' teeth. Aim of the study: The purpose of this study is to focus on evaluating the local and systemic effects of dental amalgam contained in dental fillings on human health. Materials and methods: PubMed and Google Scholar medical databases were analyzed, operating with the following keywords: dental amalgam, mercury, health effects, dentistry in as many configurations as needed. Thirty-four related articles published during the last five years (2017-2022) were selected. Results: Dental amalgam is a potential factor in many health problems among patients. Mercury's ease of penetration across the blood-brain barrier and the placenta means that it can cause adverse health effects from the prenatal period onward. Conclusions: Research on the effects of mercury from dental amalgams should continue in order to explore cause-and-effect sequences and deepen our understanding of the health implications. The search for an ideal restorative material for tooth tissue after dental treatment should be accelerated.